Interventions to enhance newborn care in north-West Ethiopia: the experiences of health care professionals - Bizuhan Gelaw Birhanu; Johanna Mmabojalwa Mathibe-Neke (BMC, 2022)
Abstract Background The provision of optimal and quality services during labour, delivery and in the early neonatal period is highly required to accelerate the reduction of neonatal deaths and improve the quality of life of newborns. The availability of competent health professionals and the essential medicines and supplies in the health facilities are compulsory. Cost-effective interventions exist to prevent more than 80% of all newborn deaths. However, an unacceptably high number of newborns are dying in the study area, and much is not known about the main contributing factors in primary healthcare settings. This study aimed to explore and describe the quality of care provided to newborns in the primary healthcare units. Methods Qualitative exploratory and descriptive design was employed. Focus group discussions were held with 26 participants (11 health workers and 15 health extension workers) in three woredas in the West Gojjam zone, Ethiopia. Health workers and health extension workers were purposely selected. Thematic analysis was undertaken. Results The primary healthcare facilities play a major role in the provision of essential services for newborns in the critical periods, including during labor and birth, immediately after birth and in the early postnatal care period. Resuscitation of birth asphyxia, prevention of hypothermia, initiation of breastfeeding, application of tetracycline, vitamin k injection, weighing babies and chlorhexidine application were identified as immediate essential intervention for the newborns. However, these interventions are hampered by factors such as lack of adequately trained staff & hands-on skills; weak referral linkage; stock-out of essential medicines and supplies and poor quality for early postnatal care home visits. Conclusions In order to enhance the quality of newborns healthcare provision, the health-systems constraints at health centres and heath posts level should be fixed to provide the required services for newborns. This requires allocation of adequate resources to tackle health facilities readiness related bottlenecks, such as the frequent stock out or lack of essential supplies, equipment, and medicines, lack of proper space for the service provision, not systematic replenishing of the revised job-aids and maintenance of medical equipment, poor infection prevention including water and sanitation in the maternity wards and newborn corners.